Implementation of mentalization‐based treatment in a day hospital program for eating disorders—A pilot study. (16th July 2021) - Zeeck, Almut; Endorf, Katharina; Euler, Sebastian; Schaefer, Laura; Lau, Inga; Flösser, Kristina; Geiger, Valeria; Meier, Alexander Ferdinand; Walcher, Peter; Lahmann, Claas; Hartmann, Armin
Abstract: Objective: Aim of the pilot study was to evaluate the effectiveness of a day hospital program for eating disorders (EDs) after implementation of mentalization‐based treatment (MBT), including a comparison to a historical matched control group. Method: All consecutively admitted patients with an ED were included in a prospective, observational study over a period of 2 years. Main outcome criteria were eating and overall psychopathology. Furthermore, changes in the capacity to mentalize (reflective functioning [RF]), difficulties with affect regulation and interpersonal problems were assessed at admission, discharge and a three months follow‐up. Results: Thirty‐eight out of fourty patients could be included. The program led to significant reductions in eating and general pathology. There was significant improvement in RF, difficulties in emotion regulation and interpersonal functioning. However, there was no advantage in comparison to a matched control group (main outcomes). ED symptoms showed a slight renewed increase after discharge, while body mass index further increased. RF change was predictive of change in overall psychopathology, but not ED symptoms. Drop‐out rate was 13.2%. Conclusion: The program showed no advantage in comparison to a historical control group concerning a reduction in eating and overall psychopathology. However, it was associated with low drop‐out rates, and changes which MBT targets: An increase in RF and a reduction of interpersonal problems as well as difficulties in emotion regulation. Highlights: Proof‐of‐concept study on a mentalization‐based treatment (MBT)‐day hospital program for eating disorder (ED). The MBT‐ED program led to an increase in reflective functioning (RF) and a reduction in difficulties in emotion regulation as well as interpersonal problems. Changes in RF were associated with changes in overall psychopathology. There was no difference in the reduction of eating and general psychopathology from admission to discharge when compared to a historical, matched control group.